When genes move farther than offspring: gene flow by male gamete dispersal in the highly philopatric bat species Thyroptera tricolor - Buchalski, Michael R. (2013)
For species characterized by philopatry of both sexes, mate selection represents an important behaviour for inbreeding avoidance, yet the implications for gene flow are rarely quantified. Here, we present evidence of male gamete‐mediated gene flow resulting from extra‐group mating in Spix's disc‐winged bat, Thyroptera tricolor, a species which demonstrates all‐offspring philopatry. We used microsatellite and capture–recapture data to characterize social group structure and the distribution of mated pairs at two sites in southwestern Costa Rica over four breeding seasons. Relatedness and genetic spatial autocorrelation analyses indicated strong kinship within groups and over short distances (<50 m), resulting from matrilineal group structure and small roosting home ranges (~0.2 ha). Despite high relatedness among‐group members, observed inbreeding coefficients were low (FIS = 0.010 and 0.037). Parentage analysis indicated mothers and offspring belonged to the same social group, while fathers belonged to different groups, separated by large distances (~500 m) when compared to roosting home ranges. Simulated random mating indicated mate choice was not based on intermediate levels of relatedness, and mated pairs were less related than adults within social groups on average. Isolation‐by‐distance (IBD) models of genetic neighbourhood area based on father–offspring distances provided direct estimates of mean gamete dispersal distances (urn:x-wiley:09621083:media:mec12593:mec12593-math-0001) > 10 roosting home range equivalents. Indirect estimates based on genetic distance provided even larger estimates of urn:x-wiley:09621083:media:mec12593:mec12593-math-0002, indicating direct estimates were biased low. These results suggest extra‐group mating reduces the incidence of inbreeding in T. tricolor, and male gamete dispersal facilitates gene flow in lieu of natal dispersal of young.